2015
DOI: 10.1111/cdoe.12193
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better understanding of dental appointment‐keeping behavior

Abstract: Appointment-keeping interventions could simultaneously address social factors that exacerbate illness and improve workflow and finances. There arises an opportunity to design innovative patient-centered interventions tailored to particular barriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…They recommend to incorporating the measured oral health literacy approach to increase the ability of understanding and decision making of the patients. 14 In several dental researches it has been evidently proved that OHL associated with better dental appointment keeping behavior, 6,23 people with dysfunctional ability to socially interact and self expression (alexithymia), 24 better children oral health status, 9 regular follow up care,(15) low prevalence of caries and periodontal disease. 5 Therefore, OHL considered as the way to access and understand oral health information, interpret the information correctly and implicate in correct decision making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They recommend to incorporating the measured oral health literacy approach to increase the ability of understanding and decision making of the patients. 14 In several dental researches it has been evidently proved that OHL associated with better dental appointment keeping behavior, 6,23 people with dysfunctional ability to socially interact and self expression (alexithymia), 24 better children oral health status, 9 regular follow up care,(15) low prevalence of caries and periodontal disease. 5 Therefore, OHL considered as the way to access and understand oral health information, interpret the information correctly and implicate in correct decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, many studies linked low OHL of the people with an overall inadequate oral health status, reduced dental appointment keeping behaviour, low understanding medicine leaflets and increased hospital admissions. [4][5][6] Understanding level of OHL is essential for bridging the communication gap between patients and dentists. 3 In Pakistan, there is limited literature that identifying barriers in local population.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research studies focusing on dental patients have found the management of pain and anxiety greatly influences their perceptions of service quality [ 24 ] and furthermore lack of attendance at appointments is largely due to anxiety around dental treatments [ 11 , 23 ]. It may be that our sample of patients reflected those with moderate to low dental anxiety, who attended their appointments and thus were able to provide data relating to their experience.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of missed dental appointments is not as simple as it appears, as the patient not only denies dental care to himself but others as well [ 4 ]. At the same time, they interrupt their continuity of care, affect workflow, waste resources, and reduce population-wide access to care [ 1 , 5 - 6 ].…”
Section: Introductionmentioning
confidence: 99%